Effect of Sugar Beet Harvest Date on Its Technological Quality Parameters by Exploratory Analysis - Lamiae Alami; Wafa Terouzi; Manar Otmani; Oussama Abdelkhalek; Souad Salmaoui; Mohamed Mbarki (Journal of Food Quality)
Choice of the harvest date is one of the foundations of vintage quality and good-yield sugar in sugar beet. However, it is difficult to define the harvest date and more precisely the date of maturity of beet roots, in an exact and absolute way. Indeed, maturity is divided into several stages and degrees depending on environmental and climatic conditions such as temperature, precipitation, geographic area, and others. The present study evoked the effect of three harvest dates (at esteemed maturity, 7 days after maturity, and 15 days after maturity) on the technological quality parameters, namely, sucrose, nitrogen, potassium, and sodium, using the most popular chemometric method, principal component analysis (PCA). To do this, samples from the Tadla irrigated perimeter were used. The results of exploratory analyses by the application of PCA clearly showed the influence of harvest date, in an important way, on the three quality parameters, composition of sucrose, potassium, and sodium. But, for nitrogen composition, there were negligible variations between samples.